The pharmaceutical professional in the middle of the COVID-19 pandemic, performance in pharmacies and drugstores (Research, Society and Development, 2023)
The objective of this work is to evaluate and discuss the proposals imposed by the Health Organs and the Federal Council of Pharmacy to the pharmacist’s performance in pharmacies and drugstores in the midst of the COVID-19 pandemic, through a documentary research. The pharmaceutical professional is located in a strategic establishment, the pharmacy or drugstore, is of wide reach in the population, which makes him/her a privileged professional. For this search, the following sites were used: National Health Surveillance Agency; Ministry of Health; Federal Council of Pharmacy. The qualitative analysis of the documents resulted in three categories for the discussion on the recommendations of pharmaceutical services in pharmacies and drugstores: the leading pharmacists in the fight against COVID-19, Pharmaceutical Care and Assistance for the Rational use of medicines and dispensing. Resulting in the dissemination of continuous and integrated activities related to the use of medicines that aim to protect, promote and recover health, in the face of the challenges of the COVID-19 pandemic.